2020
DOI: 10.1186/s13002-020-00366-4
|View full text |Cite
|
Sign up to set email alerts
|

Baby pangolins on my plate: possible lessons to learn from the COVID-19 pandemic

Abstract: The Journal of Ethnobiology and Ethnomedicine (JEET), throughout its 15 years of existence, has tried to provide a respected outlet for scientific knowledge concerning the inextricable links between human societies and nature, food, and health. Ethnobiology and ethnomedicine-centred research has moved at the (partially artificial and fictitious) interface between nature and culture and has investigated human consumption of wild foods and wild animals, as well as the use of wild animals or their parts for medic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
62
0
8

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(70 citation statements)
references
References 72 publications
0
62
0
8
Order By: Relevance
“…Eating wildlife may be a way to increase sources of protein (Asibey 1974 ). The consumption of wildlife is not uncommon in many parts of the world, including America, Africa, and Asia, and in many cases is a very important part of cultural identify (Lindsey et al 2013 ; Volpato et al 2020 ). However, the Chinese population currently have abundant choices for sources of protein.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Eating wildlife may be a way to increase sources of protein (Asibey 1974 ). The consumption of wildlife is not uncommon in many parts of the world, including America, Africa, and Asia, and in many cases is a very important part of cultural identify (Lindsey et al 2013 ; Volpato et al 2020 ). However, the Chinese population currently have abundant choices for sources of protein.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, the dangers inherent in the consumption of wildlife meat, especially if the source is unknown, should be widely publicized. As has become clear during the ongoing COVID-19 outbreak, some species of wildlife carry viruses that can cross barriers between species and mutate to become dangerous and potentially fatal to humans (Volpato et al 2020 ). Also noteworthy is that more than half of our study participants (53.7%) indicated that they thought that palm civets were carriers of SARS.…”
Section: Discussionmentioning
confidence: 99%
“…However, over the receptor‐binding domain (RBD) these pangolin viruses were more closely related to the human isolates than bat coronaviruses, suggesting pangolins as a possible intermediate host involved in the outset of the pandemic (Lam et al ., 2020). To prevent viruses spilling over from animals to humans, for example in wet food markets, wildlife sources need to be monitored and Volpato and coauthors suggest there is an urgent need for a ban on illegal pangolin but also other wild animal trade to prevent further viral spillovers (Volpato et al ., 2020; Xiao et al ., 2020). The WHO has issued recommendations to reduce risk of transmission of emerging pathogens from animals to humans in live animal markets or animal product markets (WHO, 2020b).…”
Section: The Role Of Animals In the Pandemicmentioning
confidence: 99%
“…Asia is another example of wild animals trafficking for consumption, especially in China, Myanmar, Vietnam, and Thailand, where "ye wei" ("wild taste" for wild and exotic animals) was associated with social status including in the dynastic eras as well as currently being widely sold in wet markets and restaurants, sourced legally or illegally from the wild or wildlife farms (reviewed in [72]). Important zoonoses such as some caused by coronaviruses (Table 2) have also been associated with the consumption of wild meat in markets, two of them in China.…”
Section: Wild Animals and Recent Viral Zoonosesmentioning
confidence: 99%